The Boka Kotorska: a vernacular response to sustainable urban environments - Derbyshire, Alan; Kecojevic, Tatjana (Journal of Architecture and Urbanism, 2014)
This study focuses on the development of the Boka Kotorska region of Montenegro. As such it attempts to analyse the viability of sustainable development in the region and considers the role of vernacular architecture and ecology as contributory factors. The development of the tourist industry within Montenegro is a key element within the overall strategy for economic growth. This has obvious implications for the urban development of the case study area as uncontrolled deregulated expansion threatens the future viability of attempts to create genuine environmentally sensitive planning policies. Accordingly, this study raises and discusses many of the issues faced by stakeholders in implementing innovative spatial and architectural development.